Fenomena Muenshakai sebagai Akibat Pola Hidup Individualisme serta Dampaknya terhadap Keadaan Sosial dan Ekonomi di Jepang - Roberto Masami Prabowo; Sheddy Nagara Tjandra (Bina Nusantara University, 2014)
Article described capitalist social life of modern Japanesse that was having individualistic characteristic. This high indivialistic life affected the availability of disconnected family life called muenshakai (無縁社会). This phenomenon caused social and economic shifts in the Japanese family. This research used qualitative approach elaborated in descriptive analysis. The object of research or data corpus was the problem of a decline in Japan population in terms of the breakdown of the family. The research results indicated that muenshakai phenomenon has emerged in Japan caused by some sequential events, those are: the 2nd World War “legacy”, the availability of baby boom, the abolition of shūshinkoyō (終身雇用), the decreasing of marital rate, the increasing of divorce rate, the decreasing of bith rate (少子化), and the lost of family relationship. It can be concluded that the urban individualistic life style is able to change the traditional thinking pattern into oportunistic one that becomes one of the causal factors of muenshakai phenomenon.